The Court of Justice : Reform the Justice Process for Fair and Equitable? - Laratsamee, Somphum; Yupas, Assoc. Prof. Dr. Yupaporn (Journal for Developing the Social and Community, 2017)
The right to access justice is fundamental right of every citizen in modern state which governed by the rule of law, everyone should be able to access it equally and quickly under rule of law principle that international civil law is generally enforced. Thailand’s justice system involves many government agencies and judiciary is one of relevant government agencies as well. This article focuses on issue of judicial reform in the judicial area in order to achieve fairness and equality namely; (1) Determining the duration of the operation at all stages of the judicial process is clear, so that the people get justice without delay, (2) develop mechanisms to help people access justice, (3) establish mechanisms to enforce strict laws to reduce disparities, (4) establish mechanisms to enforce the law strictly to ensure safety and fairness in society, (5) to build and develop a corporate culture to ensure fairness to the people, and (6) improve the efficiency of the justice process to enhance the competitiveness of the country.